2022
DOI: 10.1002/adhm.202202073
|View full text |Cite
|
Sign up to set email alerts
|

Design and Properties of Antimicrobial Biomaterials Surfaces

Abstract: Emergence of antibiotic-resistance pathogens has caused serious health issues and if the current trend is to continue, treatment of the infection will become complicated and even unsuccessful due to new antimicrobial resistance (AMR). Therefore, there is a global drive to identify new methods to treat infection and develop better antibacterial materials and therapy. Although new and more potent antibiotics have aided the fight against microbes, they only offer a temporary solution because future bacteria strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 434 publications
0
8
0
Order By: Relevance
“…Bacterial biofilms are steadfast gatherings of microbial organisms that instigate tenacious biofouling and biocorrosion in industrial domains and unrelenting infections that afflict humanity . To understand the dynamic process of biofilm formation, polydimethylsiloxane (PDMS) with chemically cross-linked networks (CPDMS), as one of the most popular elastomers, has been often exploited as a model material to study bacteria–material interactions due to its wide utilization in medical fields for catheters, contact lenses, medical adhesives, implants, etc. , Over the past decades, researchers have done extensive work showing that bacterial adhesions on CPDMS are regulated by various physicochemical properties of the surface, such as morphology, stiffness, and wettability. , However, most of these studies have overlooked the potential influence of uncross-linked free chains of PDMS that dissociate in CPDMS on bacterial adhesion behavior. Therefore, the majority of current investigations regarding the adherence of bacteria onto CPDMS surfaces have been conducted in bivariate circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial biofilms are steadfast gatherings of microbial organisms that instigate tenacious biofouling and biocorrosion in industrial domains and unrelenting infections that afflict humanity . To understand the dynamic process of biofilm formation, polydimethylsiloxane (PDMS) with chemically cross-linked networks (CPDMS), as one of the most popular elastomers, has been often exploited as a model material to study bacteria–material interactions due to its wide utilization in medical fields for catheters, contact lenses, medical adhesives, implants, etc. , Over the past decades, researchers have done extensive work showing that bacterial adhesions on CPDMS are regulated by various physicochemical properties of the surface, such as morphology, stiffness, and wettability. , However, most of these studies have overlooked the potential influence of uncross-linked free chains of PDMS that dissociate in CPDMS on bacterial adhesion behavior. Therefore, the majority of current investigations regarding the adherence of bacteria onto CPDMS surfaces have been conducted in bivariate circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of sharp protrusions on the surface with linear dimensions of the vertices being hundredths of microns and sufficiently far apart from each other may give them bactericidal properties, presumably due to the fact that bacterial membranes are stretched and damaged upon contact with them. This is more important for Gram-positive bacteria than for Gram-negative bacteria due to differences in their cell wall structure [ 45 , 46 , 47 ]. In some studies, the bacteriotoxicity of graphene nanoplates possessing sharp edges is also attributed to this effect [ 23 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a decrease in the number of bacteria on the surface of the material may not only indicate its anti-adhesive properties but also its bactericidal properties. Reviews by Li et al and Mehrjou et al list several piezoelectric materials for which a bactericidal effect has been shown [ 18 , 47 ]. There are a number of theories explaining the mechanisms of the microelectric field generated by the PEE on the surface of the piezoelectric material on bacterial cells.…”
Section: Resultsmentioning
confidence: 99%
“…and layered 2D materials (MXenes, graphene, black phosphorus, and their derivatives). [63] Nevertheless, the biocompatibility of materials needs to be evaluated carefully before clinical application, thus drawing the safety awareness of antibacterial PTT, as hyperthermia may also damage normal tissues. It is generally agreed that the ideal antibacterial materials should produce maximum sterilization and minimum cytotoxicity.…”
Section: Sams In Pttmentioning
confidence: 99%